The efficacy of the crude root bark extracts of Erythrina abyssinica on Rifampicin Resistant Mycobacterium tuberculosis - Bunalema, L (Makerere Medical School, 2011)
INTRODUCTION: Tuberculosis (TB) is one of the leading causes of morbidity and mortality with a global mortality rate at two million deaths per year while one third of the world's population is infected with the TB bacillus. OJECTIVE: To determine the efficacy of the crude extracts of Erythrina abyssinica root bark on rifampicin-resistant TB. METHODS: Crude extracts of root bark of Erythrina abyssinica, were screened against three strains of Mycobacterium tuberculosis including rifampicin-resistant TMC-331. Susceptibility tests used the disc diffusion method and were done on solid Middle brook 7H10, while the Minimum Inhibitory concentration (MICs) and minimum bactericidal concentration (MBCs) were determined by the Microtitre plate method using Middle brook 7H9 broth. RESULTS: The total crude methanol extract showed activity against all the three strains of mycobacterium used, at 50mg/ml and diameters of zones of inhibition of up to 26 mm. Erythrina abyssinica total crude methanol extract showed the highest activity on the pan sensitive strain H37Rv (0.39±0.0 mg/ml) and the rifampicin resistant strain (TMC-331) (2.35±1.11 mg/ ml) and was also active on Mycobacterium avium (0.39±0.mg/ml. The values for isoniazid were 0.25µg/ml and 9.38µg/ml for H37Rv and TMC-331 respectively, while for rifampicin the MIC value was 0.25µg/ml for H37Rv but it was not active on TMC-331. Acute toxicity test gave an LD50 of 776.2mg/kg body weight while the phytochemical analysis showed the presence of alkaloids, tannins and flavones. CONCLUSION: The conclusion from the study was that Erythrina abbyssinica has antimycobacterial activity and reasonable safety that merits further research.